Influência das mudanças climáticas na estrutura funcional da comunidade fitoplanctônica em um reservatório da região do semiárido - Souza, Maria da Conceição de (2014)
The Brazilian Northeast is the most vulnerable region to climatic variability risks. For the Brazilian semi-arid is expected a reduction in the overall rates of precipitation and an increase in the number of dry days. These changes predicted by the IPCC (2007) will intensify the rainfall and droughts period that could promote the dominance of cyanobacteria, thus affecting the water quality of reservoirs, that are most used for water supply, in the semi-arid. The aim of this study was to evaluate the effects of increasing temperature combined with nutrient enrichment on the functional structure of the phytoplankton community of a mesotrophic reservoir in the semi-arid, in the worst case scenario of climate change predicted by the IPCC (2007). Two experiments were performed, one in a rainy season and another in the dry season. In the water sampled, nutrients (nitrate and orthophosphate) were added in different concentrations. The microcosms were submitted to two different temperatures, five-year average of air temperature in the reservoir (control) and 4°C above the control temperature (warming). The results of this study showed that warming and nutrient enrichment benefited mainly the functional groups of cyanobacteria. During the rainy season it was verified the increasing biomass of small functional groups of unicellular and opportunists algae such as F (colonial green algae with mucilage) and X1 (nanoplanktonic algae of eutrophic lake systems). It was also observed an increasing in total biomass, in the richness and diversity of the community. In the dry season experiment there was a greater contribution in the relative biomass of filamentous algae, with a replacement of the group S1 (non-filamentous cyanobacteria with heterocytes) for H1 (filamentous cyanobacteria with heterocytes) in nutrient- enriched treatments. Moreover, there was also loss in total biomass, species richness and diversity of the community. The effects of temperature and nutrients manipulation on phytoplankton community of reservoir Ministro João Alves provoked changes in species richness, the diversity of the community and its functional composition, being the dry period which showed the highest susceptibility to the increase in the contribution of potentially toxic cyanobacteria with heterocytes